Life after COVID-19: The importance of a safe return to physical activity - Jewson, J.; McNamara, A.; Fitzpatrick, J. (Australian Journal of General Practice, 2020)
The Australasian College of Sport and Exercise Physicians has developed a guideline for primary care practitioners to assist with safe return of patients to physical activity after COVID-19.